PROSES LAY OUT KORAN DI HARIAN REPUBLIKA - Danang Arya Prayoga (Jurnal Ilmiah Publipreneur, 2014)
There are many things that need to be prepared in the process of publishing daily newspapers, starting from preparation of texts, photos, illustrations, until the process of distribution. This research describes the layout process in Republika. The layout process plays an important role in the look of a newspaper. In the process layout, there are some people who are involved, namely, managing editor, editor, photo editor, and stylist layout. Based on the experience of industry practices, everyone associated with the potentially problematic atak process so that it can interfere with the smooth running of the process say. The problem will be more severe if insufficient layout styling using software related to duties and responsibilities.